Dietary 5-hydroxytryptophan improves sheep growth performance by enhancing ruminal functions, antioxidant capacity, and tryptophan metabolism: in vitro and in vivo studies - Sun, Zhe; Aschalew, Natnael D.; Cheng, Long; Xia, Yuanhong; Zhang, Longyu; Yin, Guopei; Wang, Shikun; Wang, Ziyuan; Dong, Jianan; Zhang, Weigang; Zhao, Wei; Qin, Guixin; et al. (Frontiers in Immunology, 2024)
Hydroxytryptophan (5-HTP) can regulate the synthesis of 5-Hydroxytryptamine (5-HT) and melatonin (MT). In a previous metabolome analysis, we found that 5-HTP is an effective ingredient in yeast culture for regulating rumen fermentation. However, research on the effect of this microbial product (5-HTP) as a functional feed additive in sheep production is still not well explained. Therefore, this study examined the effects of 5-HTP on sheep rumen function and growth performance using in vitro and in vivo models. Firstly, a two-factor in vitro experiment involving different 5-HTP doses and fermentation times was conducted. Then, in the in vivo experiment, 10 sheep were divided into a control group which was fed a basal diet, and a 5-HTP group supplemented with 8 mg/kg 5-HTP for 60 days. The results showed that 5-HTP supplementation had a significant effect on in vitro DMD, pH, NH3-N, acetic acid, propionic acid, and TVFA concentrations. 5-HTP altered rumen bacteria composition and diversity indices including Chao1, Shannon, and Simpson. Moreover, the in vivo study on sheep confirmed that supplementing with 8 mg/kg of 5-HTP improved rumen fermentation efficiency and microbial composition. This led to enhanced sheep growth performance and increased involvement in the tryptophan metabolic pathway, suggesting potential benefits. Therefore, dietary 5-HTP (8 mg/kg DM) improves sheep growth performance by enhancing ruminal functions, antioxidant capacity, and tryptophan metabolism. This study can provide a foundation for the development of 5-HTP as a functional feed additive in ruminants’ production.